2012
DOI: 10.1089/dia.2012.0021
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Glucose Control with Space GlucoseControl in the Medical Intensive Care Unit—An Open Clinical Investigation

Abstract: SGC is a safe and efficient method to control blood glucose in critically ill patients in the medical intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Baseline characteristics of the Zurich population (n = 20) are given in Table 1. Baseline characteristics of the Graz population have been reported previously [28] and are similar except for a higher rate of norepinephrine and parenteral nutrition. Because of substantial national differences in informed consent procedure for patients unable to give consent at the time of study inclusion, time from ICU admission to study inclusion was significantly different between the two sites (Graz 1.7 ± 1.5, Zurich 6.7 ± 5.9 days, P = 0.001).…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…Baseline characteristics of the Zurich population (n = 20) are given in Table 1. Baseline characteristics of the Graz population have been reported previously [28] and are similar except for a higher rate of norepinephrine and parenteral nutrition. Because of substantial national differences in informed consent procedure for patients unable to give consent at the time of study inclusion, time from ICU admission to study inclusion was significantly different between the two sites (Graz 1.7 ± 1.5, Zurich 6.7 ± 5.9 days, P = 0.001).…”
Section: Resultsmentioning
confidence: 53%
“…Baseline data of the study population in Graz have been reported previously [28]. There are no significant differences between both populations with the exception of a higher rate of norepinephrine use (90 vs. 55%, P < 0.01) and a higher rate of parenteral nutrition in Graz 85 vs. 30%, P < 0.01.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…It has been integrated in the B.Braun Space GlucoseControl (SGC) system, which allows direct data communication between pumps and Space Control with the incorporated eMPC algorithm. Although SGC is already clinically used in dozens of ICUs worldwide, there are few only published experiences with its use [4]. …”
Section: Introductionmentioning
confidence: 99%